Pemeriksaan Kesehatan Dasar sebagai Upaya Deteksi Dini Masalah Kesehatan pada Santri SMK Islam Anharul Ulum Yayasan KH Dawami, Kademangan, Blitar - Wening Pangesthi Maharani; Recavery Dwi Wulandari; Nevy Norma Renityas; Dyah Mubarokah Ahadiyati; Aurel Putri Iklima; Silvia Lailatus Sa’adah; Bayu Buwana; Chairumin Alvin; Galih Syifa'ul Ummah (An-Najat, 2025)
Adolescents are an age group vulnerable to various health problems, especially in Islamic boarding schools (pesantren) environments, which present their own unique challenges. Unbalanced lifestyles, busy schedules, limited access to health facilities, and a lack of knowledge about healthy lifestyles are factors that can be detrimental to the health of adolescents in these environments. Therefore, early detection through basic health checks is a strategic step in preventive and promotive efforts. This activity aims to conduct basic health checks and education as an effort to detect health problems early in students. A total of 64 students from Anharul Ulum Islamic Vocational School underwent vital signs checks, including blood pressure, body temperature, and pulse rate, as well as a short consultation session aimed at addressing subjective complaints such as dizziness, fatigue, sleep disturbances, or other often overlooked symptoms. In addition, brief interviews were conducted to determine their dietary habits, physical activity, and rest duration. The results showed that 23.4% of students experienced hypotension, 10.9% showed symptoms suggestive of anemia, 17.2% complained of dizziness, and 10.9% experienced sleep disturbances. A total of 48.4% had no significant complaints, but were still provided with health education to raise awareness about the importance of maintaining physical and mental health. This finding underscores the importance of regular check-ups in Islamic boarding schools as part of the adolescent health support system. These check-ups not only serve as a means of identifying problems but also serve as educational opportunities that strengthen students' understanding of the importance of a healthy lifestyle. The education provided covered nutritious food selection, the importance of regular exercise, stress management, and good sleep patterns. Students responded positively to the education, with high enthusiasm and active participation during discussion sessions.